Párhuzamok jogi kultúránk zsidó-keresztény és római jogi gyökerei között : Egy interdiszciplináris kutatás kérdéseiről és módszereiről - Herger, Csabáné (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2022)
On 3 June 2022, the Faculty of Law of the University of Pécs hosted an interdisciplinary conference, where linguists, ancient historians, Roman jurists, rabbinical jurists, canon lawyers, legal philosophers and legal historians discussed the question, the influence of the Old and New Testament legal orders on the European legal culture, and the extent to which there is a parallel between the biblical and Roman legal roots of our legal culture. This volume contains 15 papers whose authors have contributed to this multifaceted discussion of this vast subject in the framework of the research project ’The Legal Relevance of the Vetus et Novum Testamentum. Parallels between the Jewish-Christian and Roman Law Roots of our Legal Culture’ of the Dezső Márkus Research Group for Comparative Legal History. In this introductory paper, the research questions and methodology are presented by the project leader.